Report on capacity strengthening training on best practices in outcome assessment, data interpretation and agricultural policy analysis - Saroj, Sunil; Vidhani, Vandana Shankar; Kumar Burman, Amit (International Food Policy Research Institute, 2025)
The Capacity Strengthening Workshop on Best Practices in Impact Evaluation, Data Interpretation, and Agricultural Policy Analysis (Phase 1) was conducted on April 22-23, 2025, aiming to build the foundational skills of fieldbased government officials in using agricultural data for informed decision-making. To strengthen its initiative on developing the Inclusive Agriculture Transformation (IAT) indicator, IFPRI has proposed a three-phased capacity-building program for key departmental staff. The objective is to enhance their understanding of the importance of data and its systematic maintenance. This initial phase focused on enhancing participants' understanding of various agricultural datasets and equipping them with basic skills in data interpretation and visualization. The workshop was inaugurated by Dr. Arabinda Kumar Padhee, Principal Secretary to Government, Department of Agriculture & Farmers’ Empowerment, Government of Odisha. The workshop was designed as part of a comprehensive capacity-building initiative to support the Inclusive Agriculture Transformation (IAT) framework, promoting evidence-based policy formulation and implementation.